RANCANG BANGUN SISTEM INFORMASI ONE STOP WEDDING SERVICE BERBASIS WEB - Bambang Hermanto; M. Gigih Periawan PS (Jurnal Pepadun, 2020)
Research on Web Design One Stop Wedding Service Information System research has been conducted with the aim to design and create a web-based information system to help people get information about wedding receptions. Creating an effective Wedding Organizer business process for clients, this information system will also help find out what items are needed at the event that takes place according to client needs. This research was developed using the waterfall method with the PHP and MySQL programming languages and testing using blackbox testing. The results of this study can be accessed directly by clients and can be used according to their interests.